Quality infrastructure investment: Ways to increase the rate of return for infrastructure investments - Naoyuki Yoshino; Nella Hendriyetty; Saloni Lakhia (Asian Development Bank Institute (ADBI), 2019)
High-quality infrastructure will boost regional economic development and reduce poverty and income inequality. The spill-over effects created by this high-quality infrastructure will be seen in the form of an increase in gross domestic product and tax revenue in the region. These positive effects can be utilized to address the gap between infrastructure demand and financing. Private−public partnerships (PPP) in infrastructure have been advocated for many years. However, PPP partners, such as insurance and pension funds, have been discouraged by the low rate of return from investing in quality infrastructure projects. This is because the main sources of revenue from infrastructure investment are user charges. This paper aims to provide a new mechanism for government and investors to utilize the spill-over effects of infrastructure projects and share them with infrastructure investors for a better rate of return in order to compensate their risk. This mechanism will motivate stakeholders to design infrastructure with high economic benefits and encourage instruments, such as city infrastructure concepts, hometown investment trusts, land trusts, and the improvement of education and digital literacy, to ensure the infrastructure projects will create positive spill-overs to the region. Hometown investment trust funds can provide financing for start-up businesses along with the new infrastructure investments. Land trusts will solve the issue of owners not wanting to sell their land by giving them the option to keep it and lease the land to infrastructure companies. The landowners can receive long-term rent income, for example for 99 years. In this way, land trusts will smoothen the use of land and transfer the usage rights to infrastructure companies.
Keywords: H54; H71; O18; 330; infrastructure; public-private partnerships; tax revenue; rate of return; land trusts